ANALISIS POLA SEBARAN DAN PERKEMBANGAN AREA UPWELLING DI BAGIAN SELATAN SELAT MAKASSAR - Inaku, Dwi Fajriyati (Torani Journal of Fisheries and Marine Science, 2015)
Waters of the southearn of Makassar Strait is a region which relatively rich of organic matter because thephenomenon of upwelling along the eastern season. The purpose of this research was to analyze the distributionpatterns and the development of upwelling areas in the southern of Makassar Strait. This study used chlorophylladata and sea surface temperature from level 1 of Modis image for two years (2009 and 2010). The resultshowed that phenomenon of upwelling that occurs in the southern Makassar Strait appears since early June, thestrongest upwelling in August and disapear in October. The upwelling was indicated by declining of sea surfacetemperature and increasing of chlorophyll-a concentration. Analysis of wind direction and speed indicate thatthe upwelling occurs in the southern Makassar strait spread to southwest with and estimated upwelling areaaround 46.000 km2.Keywords: upwelling, Makassar Strait, chlorophyll-a, sea surface temperature.